Bilateral Wilms Tumor - Case Report of a Patient with Family History - Rdzanek O; Najda P; Parysek-Wójcik K; Pytlik A; Lejman M; Zawitkowska J (The Application of Clinical Genetics)
Oliwia Rdzanek,1 Patrycja Najda,1 Karolina Parysek-Wójcik,2 Anna Pytlik,2 Monika Lejman,3 Joanna Zawitkowska4 1Student Scientific Society of Department of Pediatric Hematology, Oncology and Transplantology, Medical University of Lublin, Lublin, Poland; 2Department of Pediatric Hematology, Oncology and Transplantology, University Children’s Hospital in Lublin, Lublin, Poland; 3Independent Laboratory of Genetic Diagnostics, Medical University of Lublin, Lublin, Poland; 4Department of Pediatric Hematology, Oncology and Transplantology, Medical University of Lublin, Lublin, PolandCorrespondence: Joanna Zawitkowska, Department of Pediatric Hematology, Oncology and Transplantology, Medical University of Lublin, A. Gębali 6, 20-093, Lublin, Poland, Tel +48 507 365 635, Email joannazawitkowska@umlub.plAbstract: Wilms’ tumor (WT) is the most common renal neoplasm in children. Despite its rapid growth, it is often asymptomatic. It most commonly occurs between the ages of 3 and 5, more frequently in girls. Numerous studies report an association between the occurrence of Wilms’ tumor and genetic background. Treatment of bilateral Wilms’ tumor (BWT) presents several challenges. Recent studies raise the issue of the influence of genetics on the development of BWT. We believe that our case report is innovative as it provides information on a rare clinical presentation and comprehensively addresses the potential impact of genetic studies on favorable treatment outcomes, which are discussed only in limited detail in the literature. The case description concerns a 2-year-old and a 5-month-old patient who presented with his mother due to a change in abdominal contour. In the medical history, the boy’s mother had been treated for WT. Imaging of the abdominal cavity revealed the presence of pathological tissue changes in both kidneys. Based on this, stage V Wilms’ tumor was diagnosed. The boy underwent a right-sided tumor nephrectomy followed by a left-sided heminephrectomy. He also received pre- and post-operative chemotherapy. Genetic testing revealed a deletion fragment of exon 8 and exons 9– 10 on one allele of the WT1 gene. Despite optimistic data regarding overall survival in children with WT, a significant clinical issue remains with patients experiencing disease recurrence and bilateral BWT. Radical treatment is often required for such patients, which carries long-term consequences. Identifying patients at risk for familial WT or BWT allows for relatively early intervention and effective prevention. Furthermore, certain gene variants associated with WT can be considered prognostic biomarkers.Keywords: nephroblastoma, Wilms’ tumor, diagnostics, molecular diagnostics, treatment, children